Designing A Computer Program to Determine the Points and Planes in 3-Dimensional Projective Space - Al-Mukhtar, A. S.; Jassim, J.N. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The purpose of this work is to determine the points and planes of 3-dimensional projective space PG(3,2) over Galois field GF(q), q=2,3 and 5 by designing a computer program.